LncRNA OTUD6B-AS1 Induces Cisplatin Resistance in Cervical Cancer Cells Through Up-Regulating Cyclin D2 via miR-206 - Hou, Hui; Yu, Rong; Zhao, Haiping; Yang, Hao; Hu, Yuchong; Hu, Yue; Guo, Junmei (Frontiers in Oncology, 2021)
Cervical cancer is one of the most common gynecological cancers. Cisplatin resistance remains a major hurdle in the successful treatment of cervical cancer. Aberrant expression of long non-coding RNAs (lncRNAs) and microRNAs (miRNAs) are implicated in cisplatin resistance. However, the regulatory functions of lncRNAs and miRNAs in cervical cancer cisplatin resistance and the underlying mechanisms are still elusive. Our qRT-PCR assays verified that miR-206 levels were down-regulated in cisplatin-resistant cervical cancer cells. The introduction of miR-206 sensitized cisplatin-resistant cervical cancer cells to cisplatin. Our qRT-PCR and luciferase reporter assays showed that Cyclin D2 (CCND2) was the direct target for miR-206 in cervical cancer cells. The cisplatin-resistant cervical cancer cells expressed higher CCND2 expression than the parental cells, whereas inhibition of CCND2 could sensitize the resistant cells to cisplatin treatment. Furthermore, we demonstrated that lncRNA OTUD6B-AS1 was up-regulated in cisplatin-resistant cervical cancer cells, and knocking down OTUD6B-AS1 expression induced re-acquirement of chemosensitivity to cisplatin in cervical cancer cells. We also showed that OTUD6B-AS1 up-regulated the expression of CCND2 by sponging miR-206. Low miR-206 and high OTUD6B-AS1 expression were associated with significantly poorer overall survival. Taken together, these results suggest that OTUD6B-AS1-mediated down-regulation of miR-206 increases CCND2 expression, leading to cisplatin resistance. Modulation of these molecules may be a therapeutic approach for cisplatin-resistant cervical cancer.